Corrosion processes in cooling towers - Szymura, Teresa; Adamczyk, Wojciech (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
Corrosion testing was performed on structural steel of a cooling tower in the environment of cooling water containing ammonium sulfates and ammonium chloride. The test were performed using gravimetric and electrochemical methods with the application of a potentiostat. The analyses clearly showed that the corrosion rate is higher in solutions that contain ammonium sulfate and that the S235JRG2 steel exhibits higher corrosion resistance in this environment.